2001
DOI: 10.1037/0012-1649.37.5.654
|View full text |Cite
|
Sign up to set email alerts
|

Maternal coping strategies and emotional distress: Results of an early intervention program for low birth weight young children.

Abstract: Several questions were examined with Infant Health and Development Program (IHDP) data (N = 843). Are effects of intervention services found for maternal emotional distress and coping strategies, and are these effects different for different groups of mothers? Do maternal distress, coping, and life events moderate (or mediate) the intervention effects reported earlier for children's test scores and behavior problems (IHDP, 1990)? The intervention reduced maternal distress, especially for women with less than a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 87 publications
5
30
0
Order By: Relevance
“…Results also showed that, consistent with findings from other recent studies, White mothers and single mothers tended to be more depressed than non-White mothers and mothers in other family types (Klebanov, Brooks-Gunn, & McCormick, 2001).…”
Section: Overall Model Fitsupporting
confidence: 88%
See 1 more Smart Citation
“…Results also showed that, consistent with findings from other recent studies, White mothers and single mothers tended to be more depressed than non-White mothers and mothers in other family types (Klebanov, Brooks-Gunn, & McCormick, 2001).…”
Section: Overall Model Fitsupporting
confidence: 88%
“…Klebanov et al (2001) reported that home visiting in the first 3 years of a child's life and centerbased care in the second and third years reduced maternal emotional distress, particularly so for women with less than a high school education and those with less active coping strategies. Fuligni and Brooks-Gunn's review (2000) illustrated that economically disadvantaged children benefit from high-quality, center-based childcare programs augmented by services that support other family members and the family as a whole.…”
Section: Discussionmentioning
confidence: 98%
“…fear for the infant's life and its potential disability, helplessness, sense of losing control, feelings of guilt and injustice, anger, sadness, hope, and feeling of loss. Studies on this particular type of stress have focused not only on discovering and understanding the mechanisms responsible for the fact that some women cope with the situation of premature labor worse than others [4,7,[21][22][23], but also on discovering appropriate research tools that would allow for precise measurement of quantitative and qualitative stress [24][25][26][27]. The findings confirmed the diversification of the structure of stress experienced by the parents in the situation of premature labor.…”
Section: Introductionsupporting
confidence: 63%
“…While Affleck et al's (1989) study proposed that coping was a potential moderator of intervention efficacy, a more recent study did not. Klebanov, Brooks-Gunn, and McCormick (2001) looked at the Infant Health and Development Program data with a view to addressing (among other things) whether the impact of the intervention on low birth weight children's outcomes would be mediated by maternal emotional distress or coping. They reported that maternal coping was not influenced by the intervention and did not moderate the influence of the intervention on child outcomes.…”
Section: Introductionmentioning
confidence: 99%